Development of chiral nanomaterials and their applications for super-critical fluid chromatography - Ng, Siu Choon. (2010)
The current trend in analytical sciences focuses on application of small uniformly sized particles ranging from 1.7-5μm to be used as support materials for chromatographic separation techniques to achieve greater efficiency, lower solvent consumption, lower cost and shorter run time to improve productivity. For this project, we are exploring the application of novel chiral nanomaterials for enantiopurity analyses using SFC technique. The project focuses on the development of applications for nano-sized achiral and chiral packing materials in Super-critical fluid Chromatography (SFC). Judging from the viewpoint of novelty of science, there is to date no known research work published in open literature on the application of chiral-nanomaterials having size ranging 100-1000nm for SFC analyses. The following objectives had been fulfilled for this project, which includes i) the preparation of novel chiral stationary phase of size range 100-1000nm for SFC, ii) the preparation of new chiral and achiral nanomaterials for SFC applications, iii) the development of effective methods for packing SFC columns and iv) demonstrating rapid separations for achiral and chiral compounds using SFC.